Characterization of nebulization generated aerosol particles dispersion and deposition by total reflection X-ray fluorescence. Issue 2 (1st February 2023) - Ciniglia, Davide; Cirelli, Paola; Bilo, Fabjola; Zanoletti, Alessandra; Cornelio, Antonella; De Iuliis, Silvana; Depero, Laura Eleonora; Bontempi, Elza; Perrone, Maria Grazia; Lopinto, Paolo; Zonca, Marco; Borgese, Laura
Abstract: To prevent air pollution and achieve air quality regulations, it is essential to develop analytical techniques that can determine the concentration of metals in aerosol particles, both in the gas phase and after collection onto filters. Total reflection X-ray fluorescence spectroscopy (TXRF) and laser-induced breakdown spectroscopy (LIBS) are emerging as complementary techniques for determining the elemental composition of aerosol particles. The accuracy of their results relies on calibration methods based on aerosol and multi-element filters representative of the on-line measurement conditions and particulate collection for off-line measurement, respectively. In this paper we propose a novel methodology for characterizing nebulization generated aerosol particles dispersion and deposition by means of TXRF to assess the use of an aerosol generator to produce calibration samples for LIBS and TXRF analysis. Particles concentration and size distribution of the aerosol produced by nebulizing a Cu salt aqueous solution are measured inside a glove box modifying the production parameters and collecting the corresponding particulate deposited on reflectors. The most stable conditions are observed at average flow rate and selected for studying the aerosol spatial distribution. The Cu mass collected on reflectors positioned at a fixed distance and radial geometry with respect to the nozzle exit is measured by TXRF and increases linearly with time. Results suggest that this experimental configuration could be used to realize calibration samples for TXRF analysis representative of particulate deposition. The use of these aerosols as LIBS calibration samples could lead to significant errors due to the observed flow asymmetry. Copyright © 2022 American Association for Aerosol Research